The Semiotics and Deconstruction of the Body - Gao, Zhipeng; Abas, Imelda Hermilinda (Journal of Ecohumanism, 2024)
This paper explores the evolution of body symbolism in sculpture art since the 20th century, combining Saussure's semiotics and deconstruction theory to analyze the symbolic meanings of body imagery across different historical periods and cultural contexts. The study first reviews the representation and cultural significance of body symbols in ancient Greek and Roman, Renaissance, and Chinese ancient sculpture. It then reveals the processes of deconstruction and reconstruction of the body in modernist and postmodernist sculpture, examining the representative works of artists such as Henry Moore, Constantin Brâncuși, Antony Gormley, and Jeff Koons. Subsequently, the paper focuses on how feminist artists use body symbols to express gender, identity, and power relations, and how the application of new materials and technologies in contemporary sculpture innovates and extends body symbolism. Finally, the paper summarizes the multiple meanings of body symbols in sculpture art and proposes directions and recommendations for future research.